Internal Loads and Bioavailability of Phosphorus and Nitrogen in Dianchi Lake, China - Wu, Yalin; Huang, Tao; Huang, Changchun; Shen, Yinyin; Luo, Yang; Yang, Hao; Yu, Yanhong; Li, Ruixiao; Gao, Yan; Zhang, Mingli (Chinese geographical science, 2018)
Sediments have a significant influence on the cycling of nutrient elements in lake environments. In order to assess the distribution characteristics and estimate the bioavailability of phosphorus and nitrogen in Dianchi Lake, organic and inorganic phosphorus and nitrogen forms were analysed. The 210 Pb radiometric dating method was employed to study temporal changes in the phosphorus and nitrogen pools in Dianchi Lake. The result show that the total phosphorus (TP) and total nitrogen (TN) were both at high concentrations, ranging from 697.5–3210.0 mg/kg and 1263.7–7155.2 mg/kg, respectively. Inorganic phosphorus (IP) and total organic nitrogen (TON) were the main constituents, at percentages of 59%–78% and 74%–95%, respectively, in the sediments. Spatially, there was a decreasing trend in phosphorus and nitrogen contents from the south and north to the lake centre, which is related to the distribution pattern of local economic production. The burial rates of the various phosphorus and nitrogen forms increased in same spatially and over time. Particularly in the past two decades, the burial rates doubled, with that TN reached to 1.287 mg/(cm 2 ·yr) in 2014. As the most reactive forms, nitrate nitrogen (NO 3 -N) and ammonia nitrogen (NH 4 -N) were buried more rapidly in the south region, implying that the potential for releasing sedimentary nitrogen increased from north to south. Based on their concentrations and burial rates, the internal loads of phosphorus and nitrogen were analysed for the last century. A TP pool of 71 597.6 t and a TN pool of 81 191.7 t were estimated for Dianchi Lake. Bioavailable phosphorus and nitrogen pools were also estimated at 44 468.0 t and 5429.7 t, respectively, for the last century.